TINGKAT KEPUASAN PENGUNJUNG PADA OBJEK WISATA ALAM GUNUNG BULUSARAUNG DI DESA TOMPO BULU KECAMATAN BALOCCI KABUPATEN PANGKEP - Sukri, Muhammad Hasan; imran, Andi Nur; Djafar, Muliana (Jurnal Eboni, 2024)
Satisfaction is a feeling that arises from a person after comparing reality with expectations. Tourist attractions should prepare adequate tourist attractions with facilities and infrastructure that support tourists and good quality service, so that visitors feel satisfied, happy and in line with their expectations. This research was conducted on visitors to the Mount Bulusaraung natural tourist attraction in Tompo Bulu Village, Balocci District, Pangkep Regency. This research aims to determine the level of satisfaction of protesters. This research was carried out for 2 months, namely from September to October 2023. The method used in this research was a quantitative descriptive method with a rationalistic approach. The sampling technique uses accidental sampling technique. Data was collected using a questionnaire that had been tested for validity and reliability. The results of the study showed that the level of visitor satisfaction at the Mount Bulungsaraung Nature Tourism in Tompo Bulu Village, Balocci District, Pangkep Regency was very satisfied with a percentage of 73.3%..